The book of the pomegranate : Moses de Leon's Sefer ha-rimmon - Wolfson, Elliot R. (Brown Judaic studies, 2020)
"Hebrew edition of an important work by the Spanish kabbalist Moses de Leon (ca. 1240-1305). Sefer Ha-Rimmon, which was written in 1287, is particularly significant for study of the Zohar and the development of a theory of the commandment (mitzvot) and why one should do them."--Publisher's preface